COMPARISON OF VITAMIN D SERUM LEVELS BETWEEN PSORIASIS VULGARIS PATIENT AND NON-PSORIASIS VULGARIS PATIENTS AT HAJI ADAM MALIK HOSPITAL, MEDAN IN 2015 - Cashtry Meher; Irma DR Mahadi (Jurnal Kedokteran Ibnu Nafis, 2020)
Background: Psoriasis vulgaris is a chronic inflammatory skin disease that is multifactorial, including genetic factors, immune system defects, environmental and hormonal factors, one of which is a decrease in vitamin D levels. Vitamin D is a fat-soluble vitamin that has a steroid molecular structure. Low levels of vitamin D are associated with the incidence of psoriasis vulgaris. The purpose of this study was to determine the differences in vitamin D levels between psoriasis vulgaris patients and non-psoriasis vulgaris patients. Method: A case-control study conducted in the Dermato-immunology Division/Department of Dermatology and Venereology, Faculty of Medicine, Universitas Sumatra Utara/Haji Adam Malik Hospital, Medan. There were 11 psoriasis sufferers as cases and nine non-psoriasis sufferers as controls. Measurement of vitamin D levels was carried out using Electro Chemiluminescent Immunoassay (ECLIA). Data analysis using SPSS version 15 with independent t test. P-value <0.05 was considered significant. Result: The serum vitamin D levels in non-psoriasis vulgaris patients (33.67±2.42) were higher than the serum vitamin D levels in psoriasis vulgaris patients (16.58±6.05). There was a significant difference between both serum vitamin D levels (p = 0.0001). Conclusion: Serum vitamin D levels in psoriasis vulgaris patients were lower than serum vitamin D levels in non-psoriasis vulgaris patients, where the difference in levels is significant.